2009
DOI: 10.1038/aps.2009.40
|View full text |Cite
|
Sign up to set email alerts
|

Response of mesenchymal stem cells to shear stress in tissue-engineered vascular grafts

Abstract: Aim: Recent studies have demonstrated that mesenchymal stem cells (MSCs) can differentiate into endothelial cells. The effect of shear stress on MSC differentiation is incompletely understood, and most studies have been based on two-dimensional systems. We used a model of tissue-engineered vascular grafts (TEVGs) to investigate the effects of shear stress on MSC differentiation. Methods: MSCs were isolated from canine bone marrow. The TEVG was constructed by seeding MSCs onto poly-ε-caprolactone and lactic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 33 publications
3
52
0
Order By: Relevance
“…Specifically, the first study showed that murine MSCs subjected to a shear stress of 15 dyn/cm 2 express VEGF, but significantly decrease their expression of other growth factors -such as TGF-β1, as well as PDGF and its receptor -which are known to guide stem cells towards the SMC lineage (Wang et al, 2008). Similarly, Dong et al have shown an increase in endothelial markers at both the mRNA and protein levels, whereas SMC markers, such as SMA and calponins, decrease after subjecting canine MSCs to a shear stress of 15 dyn/ cm 2 over 2 days (Dong et al, 2009). Furthermore, the effect of shear stress on differentiation has been shown to vary depending on stress ) shear stress express endothelial markers, including CD31, vWF and VEGFR2.…”
Section: Inhibition Of Smc Differentiationmentioning
confidence: 95%
See 3 more Smart Citations
“…Specifically, the first study showed that murine MSCs subjected to a shear stress of 15 dyn/cm 2 express VEGF, but significantly decrease their expression of other growth factors -such as TGF-β1, as well as PDGF and its receptor -which are known to guide stem cells towards the SMC lineage (Wang et al, 2008). Similarly, Dong et al have shown an increase in endothelial markers at both the mRNA and protein levels, whereas SMC markers, such as SMA and calponins, decrease after subjecting canine MSCs to a shear stress of 15 dyn/ cm 2 over 2 days (Dong et al, 2009). Furthermore, the effect of shear stress on differentiation has been shown to vary depending on stress ) shear stress express endothelial markers, including CD31, vWF and VEGFR2.…”
Section: Inhibition Of Smc Differentiationmentioning
confidence: 95%
“…For example, bone-marrow-derived MSCs from a number of species are able to differentiate into endothelial-like cells when they are stimulated through physiological shear stress conditions (Engelmayr et al, 2006;Bai et al, 2010;Huang et al, 2010;Maul et al, 2011;Dong et al, 2009;Kim et al, 2011). Likewise, MSCs derived from human adipose tissue (hASCs) (Bassaneze et al, 2010;Zhang et al, 2011;Shojaei et al, 2013) and MSCs from other sources, such as amniotic fluid cells ) and human placenta (Wu et al, 2008), have also been shown to differentiate into endothelial-like cells under shear stress (see Table 1 for a summary).…”
Section: The Effect Of Shear Stress On Endothelial Cells and Mscsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, Wu et al did not report the presence of ECs or their markers, bone marrow mesenchymal stems cells (MSCs), a small portion of the mononuclear cell fraction, have been successfully differentiated into ECs in vitro (Dong et al, 2009;Moby et al, 2011). The controlled in vitro differentiation of bone marrow MSCs to smooth muscle-like and endothelial-like cells can be achieved through supplement manipulation of the culture media (Zhao et al, 2010).…”
Section: Wwwfrontiersinorgmentioning
confidence: 99%